Systematic Literature Review: Strategi Pengembangan Umkm Berbasis Teknologi Digital Untuk Keberhasilan Jangka Panjang - Nurhaliza, Iqlima (Otonomi, 2025)
The development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia plays a strategic role in strengthening the national economy. In the digital era, the integration of technology into MSME development has become essential to ensure their long-term success. This research aims to explore digital-based development strategies for MSMEs to enhance their competitiveness and sustainability. The research method used is a Systematic Literature Review (SLR) by analyzing 20 relevant journal articles from 2018 to 2023. The findings indicate that digital technology provides broad opportunities for MSMEs in terms of market expansion, operational efficiency, and innovation. However, challenges such as lack of digital skills, limited access to infrastructure, and low awareness among MSME actors remain. Therefore, the study recommends strategic efforts such as digital literacy training, digital platform development, and supportive policies from the government. This research contributes to the development of more effective strategies to encourage the digital transformation of MSMEs in Indonesia.